Predictors of Mortality in Acute Coronary Syndrome Patients: A Literature Review - Azzahra, Fadhila Nafilah; Adnan, Nurhayati (Ridwan Institute, 2023)
Acute coronary syndrome (ACS) is a serious medical condition that includes myocardial infarction and unstable angina. This study aimed to determine the factors that can predict mortality in ACS patients. This study used qualitative research methods. Data collection techniques in this study use literature study research methods obtained from Google Scholar. The data that has been collected in this study is then analyzed using three stages, namely data reduction, data presentation and conclusions. The results showed that Acute Coronary Syndrome (ACS) occurs because the coronary arteries experience the thickening of lipid plaques and can develop into Unstable Angina Pectoris (UAP), Non-ST Elevation Myocardial Infarction (NSTEMI), or ST Elevation Myocardial Infarction (STEMI). Risk factors involve age, sex, smoking, dyslipidemia, diabetes, hypertension, and obesity. Symptoms of Acute Myocardial Infarction (IMA) include chest pain, shortness of breath, and fatigue. Prognosis is influenced by treatment speed, left ventricular ejection fraction (FEVKi), and risk factors for comorbidities. Initial therapy of MONACO (Morphine, Oxygen, Nitrate, Aspirin, Clopidogrel/Ticagrelor) with statins. Administration of anticoagulants and reperfusion measures such as fibrinolysis or percutaneous coronary intervention (IKP) is important. Therapy options are adjusted to risk factors to improve prognosis.